Virtual Termination amid COVID-19: Strategies for School Social Work Interns and Field Instructors. Issue 4 (29th May 2021) - Grumbach, Giesela; Johnson, Annette H; Engel, Erik; Campos-Moreira, Linda D
Abstract: The COVID-19 pandemic disrupted the natural rhythm of the school year, affecting the way services are rendered. This shift has implications for the termination of services and the guidance of school social work interns through the termination process. This article provides lessons learned from the rapid transition from face-to-face practice to telemental health services in schools. The authors present strategies for supervising the termination process in a remote environment. In keeping with social work's professional mandate, field instructors must guide interns on conducting termination services properly and engage interns in this reflective process. This article also addresses issues of equity and access for students and their families. Attention is given to the impact of termination on student clients, families, school social work interns, and field instructors. Telemental health demonstrates promise in supporting a model of practice that provides opportunities for innovation. Researchers and practitioners are encouraged to continue this discourse for engaging in and developing best practices for telemental health services, termination of services, and supervision of social work interns in the school setting. The school social work profession must continue to augment policies related to the provision of telemental health services in school settings.